Analysis of Entrepreneurship Training in Improving Entrepreneurial Skills in Women's Empowerment Business Groups in Makassar City - Rachmawaty Kadir; Andi Izatul Fiddah; Amraeni Amraeni (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2023)
This research is to find out the extent of the implementation of women's empowerment business group training in Makassar City, how entrepreneurial activities of women's empowerment business groups in Makassar City, and what factors hinder and support entrepreneurial training of women's empowerment business groups in Makassar City. The data collection techniques used in this research are interviews, observation, and documentation. The data analysis method used is descriptive analysis. The results showed that the implementation of training provided by the National Program for Independent Community Empowerment (PNPM) Mandiri in improving entrepreneurial skills was very influential, then the entrepreneurial activities of women's empowerment business groups in Makassar City were carried out well, when training was provided by the National Program for Independent Community Empowerment in Makassar City. The inhibiting factor in this case is the lack of knowledge possessed by women's business groups in developing businesses, while the supporting factor is the spirit of cooperation from women entrepreneurs who have the desire for existing businesses in Makassar City to develop. It can be concluded that the entrepreneurship training provided by the National Independent Community Empowerment Program to empower women in Makassar City has been successful